Sprinting, strength, and architectural adaptations following hamstring training in Australian footballers - Timmins, R. G.; Filopoulos, D.; Nguyen, V.; Giannakis, J.; Ruddy, J. D.; Hickey, J. T.; Maniar, N.; Opar, D. A. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The aim of this study was to determine the sprinting, strength, and architectural adaptations following a hip-dominant flywheel (FLY) or Nordic hamstring exercise (NHE) intervention in Australian footballers. Twenty-seven male athletes were randomized to FLY (n = 13) or NHE (n = 14) training across a 39-week period (inclusive of pre-season and in-season). Biceps femoris long head (BFlh) architecture was assessed throughout. Eccentric hamstring strength and 40 m sprint times (with force-velocity profiling) were assessed at baseline, end of pre-season, and following the intervention. After the intervention, BFlh fascicle length was longer in both groups compared to baseline (FLY: 1.16 cm, 95%CI: 0.66 to 1.66 cm, d = 1.99, p < 0.001; NHE: 1.08 cm, 95%CI: 95%CI 0.54 to 1.61 cm, d = 1.73, p < 0.001). Both groups also increased their eccentric strength (FLY: mean change 82 N, 95%CI 12 to 152 N, d = 1.34, p = 0.026; NHE: mean change 97 N, 95%CI 47 to 146 N, d = 1.77, p = 0.001). After pre-season, the NHE group improved their 5 m sprint time by 3.5% (±1.2%) and were 3.7% (±1.4%) and 2.0% (±0.5%) faster than the FLY group across 5 m and 10 m, respectively. At the end of pre-season, the FLY group improved maximal velocity by 3.4% (±1.4%) and improved horizontal force production by 9.7% in-season (±2.2%). Both a FLY and NHE intervention increase BFlh fascicle length and eccentric strength in Australian Footballers. An NHE intervention led to enhanced acceleration capacity. A FLY intervention was suggested to improve maximal sprint velocity and horizontal force production, without changes in sprint times. These findings have implications for hamstring injury prevention but also programs aimed at improving sprint performance.